1979
DOI: 10.1364/ao.18.000116
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic scattering by a cluster of spheres

Abstract: A method for studying the scattering properties of a cluster of dielectric spheres is proposed. The vector scattering problem is handled through Debye potentials and a mathematical technique that accounts for multiple scattering effects. The scattered field as well as the scattering and absorption cross sections can be computed without any restriction of principle on the angle of incidence of light and on the radia and refractive indexes of the spheres in the cluster. The resulting expressions take on the well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

1980
1980
2014
2014

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(24 citation statements)
references
References 8 publications
0
23
0
1
Order By: Relevance
“…Although the theory we have developed here deals with the problem of scattering by two particles, it can be extended to the situation of more particles [26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Although the theory we have developed here deals with the problem of scattering by two particles, it can be extended to the situation of more particles [26][27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…This paper assumed that both the host medium and the particles were non-absorbing, and that the particles were much smaller than the wavelength. 13 developed a method for predicting the scatter from a cluster of spheres of arbitrary size. More rigorous methods include the T-matrix method 14,15 , which is widely used and can compute cross-sections (which can be thought of as the effective size of the particle that scatters and absorbs light) and the full polarization-dependent scattered intensity vs. scatter angle for single or multiple nonspherical scatterers.…”
Section: Multiple-scattering Modelsmentioning
confidence: 99%
“…Using this technique we can calculate scattering from molecules, from macrostructures composed of spherical particles (we model a scattering particle as an ensemble of clustered spheres), and from clouds of airborne particles (Borghese et al, 1982). In a previous publication (Borghese et al, 1978), we reported on an attempt to solve this problem by a scalar approach using the Debye potential. The resulting equations for the solution could not be solved numerically due to convergence problems inherent to the nature of the solution itself.…”
Section: Introductionmentioning
confidence: 99%